A case of pediatric cervicofacial actinomyces masquerading as malignancy: Case report and review of the literature. (January 2019) - Savoca, Emily; Mehra, Saral; Waldman, Erik H.
Abstract: Cervicofacial actinomyces is an uncommon infection, especially in children. Notoriously low culture sensitivity and malignant appearance make diagnosis challenging. Treatment requires a prolonged antibiotic course often in conjunction with surgical debridement or drainage. We report an amorphous anterior neck mass in a 10-year-old girl due to actinomyces. Diagnosis required open biopsy after non-diagnostic fine needle aspirate and core needle biopsies. The patient responded well to six-week course of parenteral penicillin followed by six months of convalescent therapy with oral penicillin. In addition to a case discussion, we review cervicofacial actinomyces in the literature with a focus on pediatrics.